Business Networking and Performance of Small and Medium Scale Enterprises in Benue State, Nigeria - Adudu, Chiangi Adudu; Indyer, Gideon Terlumun; Abdulazeez Olawale Kabiru (International Journal of Engineering and Management Research, 2021)
The impact of business networking on the performance of SMEs in Benue State, Nigeria is investigated in this study. The study focuses on the impact of network governance, network content, and network structure on SMEs in Benue State, Nigeria. The study employs a survey design, with a questionnaire serving as the data gathering tool. The study's population consists of 650 licenced SMEs in Benue State, with a sample size of 242 obtained via stratified sampling. The KMO and Bartlett's tests show that variables are highly significant, and principal component analysis was appropriate at 0.631. The reliability test-retest result revealed a reliability index of (0.702). Regression analysis was used to examine and present the data received from the businesses surveyed. Network governance (42.2 percent), network content (30.2 percent), and network structure (46.2 percent) all have a positive and significant effect on the performance of SMEs in Benue State, Nigeria, according to the results of tested hypotheses. According to the study's findings, business networking in a business environment is concerned with characteristics such as network governance, network content, and network structure, which create the foundation upon which SMEs connect with their surroundings. The research also revealed that business networking has a significant impact on SMEs' performance. SMEs working in any business environment should build up a formation structure that allows them to engage freely within the environment, according to the report.